How Are They Elected? Vote Buying And General Election In Ogan Ilir District, South Sumatera Province - Mery Yanti; Alamsyah Alamsyah (Universitas Muhammadiyah Ponorogo, 2018)
This article designed to examine patronage practice in the 2014 general election in Ogan Ilir district, South Sumatera Province, Indonesia, before and after election in one electoral area (Ogan Ilir 1). We apply Nine Step to Victory (Alamsyah, 2015) framework to achieve this goal. Our key informants are some legislative candidates and their brokerage or winning team at various level. Primary data gathered through depth interview and secondary data collected from the government institution. This data will be analyzed using interactive model (Miles, Huberman, and Saldana, 1994). Drawing on the qualitative approach, we find that, before election day, all candidates in this area practicing vote buying and patronage to get political support from the voters. A form of patronage dominated by club goods, and cash transfer (transport allowance, communication and consumption cost, and vote buying). We do not find incumbency candidate who is practicing fork barrel. After election day, especially when the winner candidates, has been working as a legislator, he has an obligation to continuing patronage through informal and cultural networking (personal or community event). In this various event, he must deliver goods, services, or money to the people (as an individual or group). Our results are strengthening the previous finding that all candidates have begun implementing patronage strategy when they are recruiting the winning team, campaign, and realize vote buying. Family, especially extended family, and friendship is the primary foundation for all candidates to build brokerage (the winning team) structure. All candidates also using “by name by address” strategy to guide vote-buying practice. We discuss this finding, showing limitation and agenda for the research on this topic.